(untitled) (Experimental biology, 2025)
The paper presents new data on the influence of regulatory factors on the biomorphological development of Stevia rebaudiana plants, which are widely cultivated worldwide for the production of natural sweeteners. Stevia has attracted attention due to its non-toxicity, biological activity and lack of harmful effects. In order to develop disease resistant stevia varieties with desirable traits along with traditional breeding, biotechnological approaches are being actively developed. Research on stevia cultivation is gaining importance in the context of its potential as a safer alternative to synthetic sweeteners derived from sugars with negative health effects and in the treatment of chronic diseases such as diabetes mellitus. The studies conducted revealed important factors determining the effectiveness of growth regulators on the morphogenesis of S. rebaudiana. The paper presents biotechnological methods, including in vitro micropropagation, which offer opportunities for large-scale production, development of new varieties and conservation of valuable genotypes. ...